The polygenic risk for obsessive-compulsive disorder is associated with the personality trait harm avoidance. - Bey, Katharina; Weinhold, Leonie; Gruetzmann, R.; Heinzel, S.; Kaufmann, C.; Klawohn, Julia; Riesel, Anja; Lennertz, L.; Schmid, Matthias; Ramirez, Alfredo; Kathmann, N.; Wagner, Michael (Acta Psychiatrica Scandinavica, 2020)
OBJECTIVE: Obsessive-compulsive disorder (OCD) is a complex psychiatric disorder with a substantial genetic contribution. While the specific variants underlying OCD's heritability are still unknown, findings from genome-wide association studies (GWAS) corroborate the importance of common SNPs explaining the phenotypic variance in OCD. Investigating associations between the genetic liability for OCD, as reflected by a polygenic risk score (PRS), and potential endophenotypes of the disorder, such as the personality trait harm avoidance, may aid the understanding of functional pathways from genes to diagnostic phenotypes. METHODS: We derived PRS for OCD at several P-value thresholds based on the latest Psychiatric Genomics Consortium OCD GWAS (2688 cases, 7037 controls) in an independent sample of OCD patients (n = 180), their unaffected first-degree relatives (n = 108) and healthy controls (n = 200). Using linear regression, we tested whether these PRS are associated with the personality trait harm avoidance. RESULTS: Results showed that OCD PRS significantly predicted OCD status, with patients having the highest scores and relatives having intermediate scores. Furthermore, the genetic risk for OCD was associated with harm avoidance across the entire sample, and among OCD patients. As indicated by mediation analyses, harm avoidance mediated the association between the OCD PRS and OCD caseness. These results were observed at multiple P-value thresholds and persisted after the exclusion of patients with a current comorbid major depressive or anxiety disorder. CONCLUSION: Our findings support the polygenic nature of OCD and further validate harm avoidance as a candidate endophenotype and diathesis of OCD.
EVALuna2:422265